Biological accidents in a Peruvian university medical students: prevalence, mechanisms and risk factors - Inga, Elizabeth (2010)
Introduction: One of the most serious problems of medical students is occupational exposure during their clinical training as they lack experience and limited development of hand skills. Objectives: To establish the frequency, mechanisms, circumstances and risk factors of biological accidents reported in medical students. Design: Descriptive observational transversal type study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Medical students. Methodology: A retrospective anonymous and voluntary survey was conducted. Study participants were randomly chosen. Main outcome measures: Biological accidents. Results: In a sample of 307 students 51,5% had at least one accident (158/307); median of biological accidents in the last year was 1,06; 91,1% of senior students had at least one biological accident last year versus 11,9% of first-year students. Senior students inform more often about high-risk infection-transmission accidents, 47,6% caused by pinching with a sharp object while 80,6% were exposed to blood; high-risk accidents are far more often in surgical and delivery rooms (51,9%). Conclusions: It is necessary to develop strategies that allow medical students to enforce biosecurity concepts.